The Pucará of Aconquija «Which They Call the Inga’s» and the People of Malle in the Southeastern Frontier of Tawantinsuyu - Patané Aráoz, Claudio Javier (2017)
The analysis of the nuances of the Inca conquest in the southern Andes has received consistent attention from both archaeologists and historians. Recent studies carried out in different regions of Collasuyu have evaluated the relationship between expansionary policies, systems of defense, and ethnic interaction in borderland contexts. These studies have generated promising areas of debate. In this paper I present results of archaeological studies and analysis of historical sources related to the Pucará of Aconquija (Catamarca, Argentina). This site is one of the most important Inca fortresses located on the southeastern frontier of Tawantinsuyu.